Case histories - Atkinson, Kate.; Black Swan. (London : Black Swan, 2005)
Private detective Jackson Brodie uncovers some startling connections between three separate cases he is investigating.
Adult
Keywords: Fate and fatalism -- Fiction; Loss (Psychology) -- Fiction; Domestic fiction; Love stories